Taxas de perdas de solo e água em um latossolo argiloso sob sistema plantio direto - Celante, Luana Salete (2017)
Erosive processes have been a constant concern in relation to soil management and use, especially with reflections on crop yield and environmental quality, mainly due to the soil and water losses from runoff. Thus, the objective of the present work was to quantify soil and water loss rates in a clayey Oxisol under no-tillage system, relating these rates to soybean grain yield and to develop models that associate water and soil loss rates depending on the slope variation. The experimental area is located in a municipality of Cascavel - PR, commercial crop of soybeans. The treatments were four pre-established slope of 3.5%, 8.2%, 11.4% and 13.5% which were monitored water and soil loss rates at different rainfall events. The soil and water losses were collected in gutters made of PVC and stored in containers for measurement and analysis. The obtained data were statistically evaluated by the Tukey test. There was no significant influence of the slopes used in the different rain intensities, in the water and soil losses. There was a difference in soybean grain yield in which treatments with slopes 8.2% and 13.5% showed higher values. The loss of soil and water presented a higher correlation with macroporosity and soil density together. The soybean grain yield presented a higher linear correlation with the loss of water and soil. The low water and soil losses demonstrate the soil capacity, managed under the no-tillage system, to minimize environmental impacts.